High-Density DArT Markers and Phenotypic Characterization of Cowpea Accessions (Vigna unguiculata (L.) Walp) - B. G. Adu; R. Adu Amoah; L. M. Aboagye; M. G. Abdoul Aziz; R. Boampong (Advances in Agriculture)
Cowpea (Vigna unguiculata (L.) Walp) is an important component of most traditional cropping systems in the tropics. It provides leafy vegetables and/or grains and forages and acts as a cover crop. We characterized 16 cowpea accession collections in Ghana using agromorphological traits and high-density silicoDArT markers for breeding and efficient conservational purposes. Principal component analysis indicated pod, leaf, and seed characters such as pod length, seeds per pod, terminal leaves shape, number of leaves, hundred seed weight, and seed weight per plant as discriminatory traits in revealing the variation among the accessions. Trait association analysis revealed a significant correlation between the pod number, pod length, seeds per pod, number of leaves, and seed weight per plant that could allow the selection to improve the grain yield. Moderate to high broad-sense heritability and genetic advance observed for most of the traits indicate that the selection would result in foreseeable genetic improvement. The 9,706 silicoDArT markers used in the study were able to reveal genetic variation among the tested cowpea collections. Accessions GH5039 and GH6056 were established as duplicates based on the silicoDArT markers, which could enhance efficient germplasm utilization and conservation. Accessions GH3685, GH3674, and GH4541 were identified for high leaf and pod production and high seed yield per plant, which could be good candidates for dual purpose cowpea production, which is common in the subsistence farming system.